Réponses

2013-12-30T09:16:20+01:00
C=1/4+5/6/1/2-1/3
=1/4+5/6*2-1/3
=1/4+10/6-1/3
=3/12+20/12-4/12
=19/12

d=1-1/3+1/4/1+1/3-1/4
=1-1/3+1/4+1/3-1/4
=1

e=2/9+1/9*4/2/3-1/6+4/9
=2/9+1/9*2/3-1/6+4/9
=2/9+2/27-1/6+4/9
=6/27+2/27+12/27-1/6
=20/27-1/6
=120/162-27/162
=93/162
=31/52

f=(1-1/3)*7/1-1/3*7
=(3/3-1/3)*7-7/3
=2/3*7-7/3
=14/3-7/3
=7/3

g=5/9+2/3*7/4/5/9-11*3/44
=5/9+14/12*9/5-33/44
=5/9+126/60-33/44
=5/9+21/10-3/4
=200/360+956/360-270/360
=886/360
=442/180
=221/90

h=3*1-2/7*3+1/3/1-1/6*3-3/7
=3-6/7+1/3-3/6-3/7
=3-9/7+2/6-3/6
=3-9/7-1/6
=126/42-54/42-7/42
=65/42